SNAKE BITE WITH A FATAL OUTCOME IN WESTERN SERBIA – A RARE CASE REPORT - Pavic, Sladjana; Tomic, Branko; Novkovic, Aleksa; Ajtic, Rastko; Nikolic, Sonja (Medical Research, 2026)
Introduction: Snakebites can lead to a wide range of clinical manifestations, from local tissue effects to systemic complications, including rhabdomyolysis, coagulopathy, acute kidney injury, neurological, and cardiac events. Although snakebites in Western Serbia are generally not a major public health issue, severe cases may occur, with potentially fatal outcomes.Patient review: We report the case of a 71-year-old man bitten by Vipera ammodytes in ####, Western Serbia. He presented with fatigue, vomiting, and swelling of the left hand one hour after the bite. His past medical history included diabetes mellitus, ischemic stroke, and cerebral aneurysm repair. On admission, he was hypotensive and dehydrated, with a local hematoma and thrombocytopenia. He received antivenom, corticosteroids, dopamine, antibiotics, and supportive care. Despite initial stabilization, the patient developed acute respiratory distress, acute kidney injury, hypotension, and peripheral cyanosis, requiring mechanical ventilation and dual inotropic support. Laboratory findings indicated coagulopathy and rising markers of organ injury. Despite intensive management, the patient succumbed to complications.Conclusion: This represents the first reported fatal snakebite in Western Serbia in the past 30 years. The primary pathogenic mechanism was likely disseminated intravascular coagulation triggered by the venom. This case highlights the importance of prolonged clinical and laboratory monitoring, timely supportive therapy, and awareness of severe systemic complications following snakebites, even in regions with historically low incidence.
Keywords: Cardio- and cerebrovascular damages, comorbidities, diabetes mellitus, nose-horned viper (Vipera ammodytes), snakebite envenoming